The first disease connection for Cav2.2 channels - Weiss, Norbert (General physiology and biophysics, 2015)
Commentary to: CACNA1B mutation is linked to unique myoclonus-dystonia syndrome. (Hum. Mol. Genet. 2015, pp. 987-993).
Keywords: vztahy mezi strukturou a aktivitou; Molecular Sequence Data; Humans; Genetic Predisposition to Disease; genetická predispozice k nemoci; Mutation; Structure-Activity Relationship; srdeční arytmie; Ion Channel Gating; vápníkové kanály - typ N; Dystonic Disorders; sekvence aminokyselin; Calcium Channels, N-Type; gating iontového kanálu; dystonické poruchy; molekulární sekvence - údaje; Amino Acid Sequence; lidé; Arrhythmias, Cardiac; mutace